NURTURING THE ACADEMIC PERSONA FOR THE NATION’S HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 14 December 2015 – Leadership academic persona of academicians in institutions of higher learning need to be nurtured to produce academicians who are capable of initiating changes in higher education and to realise their changing role of transferring knowledge they have acquired in the universities to the society.